Rekomendasi Pemilihan Burung Menggunakan Metode Simple Additive Weighting (SAW) dan Technique Order Preference by Similarity To Ideal Solution (TOPSIS) - Rizal Rudiantoro; Imam Cholisoddin; Ratih Kartika Dewi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The melodious bird is in great demand for a group of animal lovers, for a group of bird lovers the price of birds can reach an expensive price for one type of bird that has a sweet voice. In social media, there are so many singing bird sellers that promote various kinds of singing birds. Many of Indonesian people have been moved from offline birds market to social media to buy birds because it's easier to choose the type and price of birds. This research makes a system which able to find the criteria for singing bird recommendation that appropriate to the bird lovers. To implement a singing bird recommendation system there is a need for a method to find the best, accurate, and precise recommendation. This system uses Simple Addictive Weighting (SAW) and Technique Order Preference by Similarity to Ideal Solution (TOPSIS) method. This system has been tested trough Spearman Correlation get significant results from 3 kinds of birds e.g Green Lovebird: 6,34, Green Cucak 4,92, Kacer: 5, 80 with value Î±=1,96. The final result from this system recommends the first rank bird based on the highest preference score.